Os saberes docentes e a exploração sexual comercial de meninas: desafios da contemporaneidade - MARTINS, Railda Gonçalves (2010)
This work is part of the Line Research Training and Professionalization. The goal of research is to know the values that teachers express when dealing with the adolescent involved with commercial sexual exploitation. The teacher and presents as key characters in the process of socialization of the individual, since the school is composed of individuals with certain historical realities, social and cultural references which directly influence the construction and assimilation of values by their students. To read those values, bibliographic searches were conducted and field. In literature, the path query classical and contemporary authors who have focused on studies related to the subject, but also investigations that have as object of study the issue of sexual exploitation of teenagers, both in Brazil and abroad. Regarding the training of teachers and professors, the discussion focused on the teacher knowledge, and as support for their understanding, works by authors who deal with this issue. This is a qualitative research in which empirical study took place in two schools in the municipality of Goiânia-GO. The data collection instruments used were questionnaires, videos related to the issue of commercial sexual exploitation of adolescents (ESCCA) and focus group technique. Data collected and analyzed revealed that the teachers and know the difference between prostitution and ESCCA. Compared to what to do when they realize ESCCA cases, it was evident that they do not know what to do and how to refer the problem to instances of defense and protection, such as child protection agencies, and know their role and how to establish links with this instance . With respect to situations in which adolescents are involved in ESCCA realizes that some teachers have difficulty understanding that the adult is responsible. Indicate that the family played a more rigorous and that now is different, because they lack authority that commands a person, whether or father or mother. Express that sexuality is more present and that the media reinforces these issues influencing adolescents and efficiently disposed of, the girls are involved in ESCCA lack of religion. It was found that academic education is not subsidized, theoretically and practically, teachers to deal with ESCCA, and they draw on knowledge from the professional practice of magazines and newspapers, talking with family, friends, schoolmates, television and, the Church. The data showed that the political-pedagogical project of the two schools does not address the issue of sexual violence, especially ESCCA, although schools in which this reality is present.